2016
DOI: 10.2500/ajra.2016.30.4377
|View full text |Cite
|
Sign up to set email alerts
|

Role of Lumbar Drains in Contemporary Endonasal Skull Base Surgery: Meta-Analysis and Systematic Review

Abstract: Available evidence for the use of LDs in skull base surgery is of poor quality. Analysis of the literature revealed heterogenous and varied reporting in the primary literature. Further studies that include randomized controlled trials are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 44 publications
1
48
0
1
Order By: Relevance
“…16 Perioperative CSF lumbar drainage represents one way of potentially mitigating this risk. 20,35 With CSF leak rate reduction through use of vascularized pedicled flaps in reconstruction, there has been a reported reduction of LD usage with emphasis on placement in response to specific reconstruction, flow of CSF leak, and surgeon preference. 23,36 Our survey indicated more respondents place LDs preoperatively as the perceived risk of postoperative CSF leak increases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Perioperative CSF lumbar drainage represents one way of potentially mitigating this risk. 20,35 With CSF leak rate reduction through use of vascularized pedicled flaps in reconstruction, there has been a reported reduction of LD usage with emphasis on placement in response to specific reconstruction, flow of CSF leak, and surgeon preference. 23,36 Our survey indicated more respondents place LDs preoperatively as the perceived risk of postoperative CSF leak increases.…”
Section: Discussionmentioning
confidence: 99%
“…23,36 Our survey indicated more respondents place LDs preoperatively as the perceived risk of postoperative CSF leak increases. Contradicting this logic is the recent meta-analysis by D'Anza et al, 35 which found that LD use was not associated with a reduced odds ratio for postoperative CSF leak. When postoperative CSF leak occurs, our respondents attempt conservative management with lumbar drainage an average of 2.5 days, consistent with published recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…At some centers, it is used routinely with good success, predominantly for larger high‐grade leaks, whereas in others it may be associated with a higher failure and meningitis rate . Two recent meta‐analyses and a review article failed to find benefit of perioperative lumbar drain placement in patients with pituitary adenomas and other skull‐base tumors, and 1 emphasized potential risk of major complications including meningitis and ventriculitis . However, there is also conflicting data showing that use of intraoperative LD may reduce the risk of intraoperative CSF leak .…”
Section: Intradural Tumorsmentioning
confidence: 99%
“…Complications after EESBS such as CSF leak can lead to costly readmissions and disrupt patient recovery, yet routine intraoperative practices such as the use of LDs and reconstructive techniques have not yet been standardized. Meta‐analyses have not shown any significant decrease in postoperative CSF leak when an LD was used in routine pituitary surgery . Similarly, a more recent large retrospective review showed no decrease in perioperative CSF leak rates in those patients undergoing lumbar drainage .…”
Section: Discussionmentioning
confidence: 95%